Differences in Body Composition of Upper and Lower Limbs in Elite Taekwondo Athletes - Jeon,MinSoo (Sociedad Chilena de Anatomía, 2020)
SUMMARY: In this study, we analyzed the differences in body composition among athletes during different stages of their career Forty taekwondo athletes and 10 non-athletes (20 males and 30 females) with a mean age of 18.2 years (range, 15-23 years), a mean height of 173.4 cm, and a mean body weight of 64.8 kg were studied using dual energy X-ray absorptiometry and Biodex balance system. The bone mineral density of upper and lower limbs was higher among university athletes of both sexes than in high school athletes. The lean body mass of male athletes in the university was higher than in high school male athletes. By contrast, in case of females, the opposite results were obtained for the upper and lower limbs. Elucidation of the body composition according to career and sex of taekwondo athlete is worthwhile.